A taxonomic overview of Notylia platyglossa Schltr. and related species (Orchidaceae) - S. De Oliveira, Miguel; H. Krahl, Amauri; B. F. Silva, João; Krahl, Dayse R.p.; L. Viana, Pedro; Meneguzzo, Thiago E. C. (Phytotaxa, 2024)
In this study, through a review of the literature, analysis of protologues, field collections and consultations of herbariums, we elucidated the Notylia platyglossa species complex. We propose the synonymization of the names N. peruviana, N. morenoi under N. platyglossa. Additionally, we designated lectotypes for N. peruviana and N. morenoi as well as neotypes for N. platyglossa and N. boliviensis. We also distinguished N. boliviensis from N. platyglossa and validated the first record of this species for Brazil. Descriptions, taxonomic comments, distribution maps, photographic plates and the conservation status of these species are also presented.